Analyzing the Benefits of Optical Topology Programming for Mitigating Link-Flood DDoS Attacks - Nance-Hall, Matthew; Liu, Zaoxing; Sekar, Vyas; Durairajan, Ramakrishnan (IEEE transactions on dependable and secure computing, 2025)
Link-flood attacks (LFAs) overwhelm bandwidth on links in a network using traffic from many sources, which is indistinguishable from benign traffic. Unfortunately, traditional DDoS defenses are incapable of stopping such attacks and recently proposed software-defined solutions are ineffective. In this work, we observe a new opportunity for mitigating LFAs using optical networking advances. In essence, we envision new capabilities for topology programming , to scale capacity on-demand to avoid congestion and add new links to the network to create new paths for traffic during LFA incidents. Realizing these benefits of optical topology programming raises unique challenges; the search space for candidate topology configurations is very large and joint optimization of topology and routing is NP-hard. We present ONSET-a framework that tackles these challenges to lay a practical foundation for topology programming-based defenses against LFAs. We show that ONSET complements existing programmable network defenses and amplifies their benefits. We perform a what-if style analysis of ONSET by simulating a wide-ranging set of attacks, including terabit-scale attacks against every single link, on five networks with two different routing capabilities and observe that ONSET provides the means to mitigate congestion loss in more than 90% of the hundreds of diverse attack scenarios considered.